Effect of acupuncture therapy on body composition parameters / Kamrun Nahar - Kamrun, Nahar (2012)
Acupuncture is a technique for inserting needles into the body to introduce anesthesia or reduce pain. In detail, acupuncture basically is a procedure involved with stimulation of anatomical locations on or in the skin by using different types of techniques. Acupuncture is used for maintaining condition of body or treats human diseases for thousands of years.This thesis concerns the bioimpedance parameters (BI) and body composition parameters of people before and after undergoing acupuncture therapy. To measure bioimpedance (BI) parameters of normal subject and patients before and after acupuncture therapy I need to calculate the body composition parameters using Quadscan 4000. Also I need to make an analysis and comparison between BI parameters before and after acupuncture therapy. The main purpose of this study is to investigate the effect of acupuncture before and after acupuncture in term of resistance (R); reactance (X); impedance (Z); Phase angle; and capacitance (C) of female and male subjects that can be measured as bioimpedance (BI) parameters. The body composition parameters included with Fat Free Mass (FFM); Intracellular Water (ICW) Fat Mass (FM); Total Body Water (TBW); Extracellular Water (ECW) Basal Metabolic Rate (BMR) and are calculated based on bioimpedance (BI) parameters. All these parameters analyzes by using statistical analysis program called SPSS.